1988
DOI: 10.1159/000167585
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Parathyroid Hormone on Random Migration of Human Polymorphonuclear Leukocytes

Abstract: Derangements in leukocyte function occur in patients with primary hyperparathyroidism and in those with uremia, which is a state of secondary hyperparathyroidism, suggesting that parathyroid hormone (PTH) may affect leukocyte function. We examined the interaction between PTH and random migration of human polymorphonuclear leukocytes (PMNL) utilizing a modified Boyden chamber. Intact 1–84 PTH but not its amino-terminal (1–34 PTH) or its carboxy-terminal (53–84 PTH) fragments produced marked and significant (p <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Analysis of our data, while speculative at this point, suggests that PTH administration neutralizes LPS-mediated inflammation. In this regard, analysis of the data collected over the last decade indicates that PTH may act as an immunomodulating hormone (Doherty et al, 1988). For example, random migration of polymorphonuclear leukocytes (PMNLs) is impaired in chronic renal failure (CRF) patients, and an inverse relationship exists between random migration of PMNLs and blood levels of PTH in these patients (Doherty et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of our data, while speculative at this point, suggests that PTH administration neutralizes LPS-mediated inflammation. In this regard, analysis of the data collected over the last decade indicates that PTH may act as an immunomodulating hormone (Doherty et al, 1988). For example, random migration of polymorphonuclear leukocytes (PMNLs) is impaired in chronic renal failure (CRF) patients, and an inverse relationship exists between random migration of PMNLs and blood levels of PTH in these patients (Doherty et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, analysis of the data collected over the last decade indicates that PTH may act as an immunomodulating hormone (Doherty et al, 1988). For example, random migration of polymorphonuclear leukocytes (PMNLs) is impaired in chronic renal failure (CRF) patients, and an inverse relationship exists between random migration of PMNLs and blood levels of PTH in these patients (Doherty et al, 1988). Moreover, it is possible that PTH affects leukocyte functions directly, since both B-and T-cells contain receptors for the hormone (McCauley et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators reported impaired phagocytosis with the defect residing in the PMNL [1,2], while others found that the serum of uremic patients contains an inhibitor of phagocytosis [3][4][5], In contrast, several stud ies could not confirm defective phagocytosis in CRF [6, affects random migration of these cells [12] as well as their degranulation [13]. It is theoretically possible that the high blood levels of PTH in CRF patients affect the phagocytic function of their PMNL.…”
Section: Introductionmentioning
confidence: 99%
“…A link between PTH and immune function has been suggested since immune cells such as T and B lymphocytes and leukocytes express PTH receptors (21, 22) . In fact, neutrophils from patients with hyperparathyroidism exhibit defects in chemotaxis, migration, and phagocytosis (23-25) and these defects are rescued when parathyroidectomy is performed (26). Thus, the concept that PTH is a negative modifier of the host immune system has been established (27, 28).…”
Section: Discussionmentioning
confidence: 99%